Oro-facial lesions and CD4 counts associated with HIV\AIDS in an adult population in Oyo, state, Nigeria (2004)
The objective of this study was to define the oro-facial lesions associated with Human Immunodeficiency Virus (HIV)/Acquired Immune Deficiency Syndrome (AIDS) in an adult population in Oyo state, Nigeria and to relate these with the level of immune suppression as measured by the CD4 counts.MATERIALS AND METHOD:The study population consisted of 679 consecutive subjects who were seen at the state-owned blood bank. Information on demography, medical and medication histories were obtained. Oro-facial examinations were carried out according to Greenspan et al [Oral Surg Oral Med Oral Pathol (1992)73:142-144]. HIV sero-prevalence status was determined for all patients. CD4+ T-lymphocyte count was carried out for those sero-positive for HIV and 31 randomly selected HIV-negative subjects. Data were analyzed using the chi-square test, Fisher's exact test, Student's t-test and odds ratio where appropriate.RESULTS:Eighty-one (11.9%) of the entire study sample were confirmed HIV positive. The prevalence of specific oral lesions by HIV sero-status revealed that pseudomembranous oral candidiasis and angular cheilitis occurred significantly and more frequently in HIV-positive subjects (33.3 and 21% respectively) than those who were HIV negative (4.3 and 1.8% respectively, P < 0.05). The mean CD4 count of the HIV-positive subjects was 452 cells mm(-3), s.d. 137, while it was 602 cells mm(-3), s.d. 251, for the HIV negatives. The difference was statistically significant (P = 0.000). Forty-four (66.7%) subjects with CD4 counts <500 cells mm(-3) had oro-facial lesions whereas among those with CD4 counts >500 cells mm(-3) only 22 (33.3%) had oro-facial lesions (OR = 4.57).CONCLUSION:The type of oro-facial lesions most commonly associated with HIV/AIDS in Oyo state, Nigeria, has been shown to be pseudomembranous oral candidiasis. This was followed by angular cheilitis. These lesions, although found in HIV-negative subjects, were in a lower proportion as compared with HIV-positive subjects. Mean CD4 counts were lower in HIV-positive subjects and this was associated with greater prevalence of oro-facial candidiasis and angular cheilitis.